Virtual Reality for Veteran Relaxation (VR2) – Introducing VR-Therapy for Veterans With Dementia – Challenges and Rewards of the Therapists Behind the Scenes - Appel, Lora; Appel, Eva; Kisonas, Erika; Pasat, Zain; Mozeson, Khrystyna; Vemulakonda, Jaydev; Sheng, Lacey (Qing) (Frontiers in Virtual Reality, 2021)
Background: Veterans who suffer from post-traumatic stress disorder have an increased risk of dementia, and many of those with dementia are eventually placed in long-term-care. Responsive behaviours such as physical and verbal aggressiveness are often exhibited by people with dementia, and negatively impact clinical outcomes, contribute to caregiver/staff burnout, absenteeism, low engagement, and elevated risk of abuse or neglect. Virtual Reality (VR) is explored as a non-pharmacological therapy for those with dementia. Studies are evaluating clinical outcomes, but the challenges and learnings of the staff who administer VR-therapy remain under-reported. Objective: To capture the experiences of the recreational therapists (RTs) who conducted study sessions and administered VR-therapy to residents with dementia at the Perley and Rideau Veterans’ Health Centre. Specifically, we collected RTs’ feedback on the process of conducting the trial, including technical, environmental and personal challenges, learnings, what were successful elements, and their recommendations. Methods: This qualitative study employed in-depth semi-structured interviews, conducted remotely with seven RTs at Perley Rideau. The interviews followed a predefined script, were audio-recorded, transcribed, anonymized, and analyzed with the aid of a qualitative data analysis tool. Two independent researchers coded the interviews into themes using a constant comparative method/grounded theory approach. Results: RTs reported ease in learning the VR technology, and faced only minor technical problems with the equipment. The main challenges were due to unfamiliarity and insufficient time allocated to conducting research. Targeted sessions were particularly difficult to conduct due to the requirement for joint presence of various staff, often on short notice. RTs emotional reactions, such as uneasiness to place the VR headset on frail individuals in distress, often hindered their ability to administer VR-therapy. Positive impact of VR-therapy on managing responsive behaviours was observed in participants with responsive behaviours related to physical pain, more so than emotional distress. Conclusion: Failure to consider the experiences of these vital stakeholders when developing novel interventions contributes to the gap between efficacy in research and effectiveness in practice. Feedback received from RTs in this study provides critical information to support successful, sustainable implementation of VR-therapy, both for further evaluation and as a regular activity program.